The relationships between pre- to syn-Pampean orogeny metasedimentary rocks in the Eastern sierras Pampeanas (Argentina) - Casquet, C.; Rapela, C.; Baldo, E.; Pankhurst, R.; Galindo, C.; Verdecchia, S.; Murra, J.; Dahlquist, J. (2024)
Fil: Casquet, C. Universidad Complutense. Instituto de Geociencias. Departamento de Petrología y Geoquímica; España.